Soot and NO emissions control in a natural gas/diesel fuelled RCCI engine by φ-T map analysis. Issue 2 (4th March 2017) - Li, Jing; Yang, Wenming; An, Hui; Zhou, Dezhi
Abstract : Soot and NO emissions are considered as major pollutants to the atmosphere from compression ignition engines. Researchers have been dedicated to the reduction of soot and NO emissions. Thus, an advance combustion regime, i.e. reactivity controlled compression ignition (RCCI), was proposed to mitigate the formation of these emissions. In this study, the dynamic ϕ-T (equivalence ratio vs. temperature) map analysis was applied to visualise the combustion processes associated with the in-cylinder temperature and equivalence ratio in an RCCI engine. Therefore, the soot and NO emissions can be efficiently reduced by controlling the combustion process out of the emissions islands on the ϕ-T map. This analysis method employs KIVA4-CHEMKIN and SENKIN code to construct ϕ-T maps under various conditions. To find out the significant parameters of controlling combustion process and emissions formation, four parameters were taken into consideration in a natural gas (NG) and diesel fuelled RCCI engine: NG percentage, the first start of injection (SOI) timing, split fraction of diesel and exhaust gas recirculation (EGR) rate. Each parameter was varied at three levels. Finally, the ϕ-T maps and final soot and NO emissions were compared among varied conditions for each parameter. It is found that the increased NG percentage can significantly reduce soot because of the absence of C-C bond in NG and the reduced diesel fuel impingement on the surface of the piston or cylinder wall. Increasing EGR can decrease the peak combustion temperature due to the dilution effect and thermal effect, consequently maintaining RCCI at low temperature combustion region. This study also indicates that dynamic ϕ-T map analysis is efficient at manipulating the combustion process to mitigate the soot and NO emissions formation.